Discrete element simulation analysis of ball mill ball trajectory and liner plate structure based on EDEM - Shen, Jun; Li, Wenwei; Deng, Weina; Huang, Mingrong (Edelweiss Applied Science and Technology, 2025)
The ball mill is the preferred equipment for ore grinding, and research on ball mill grinding technology can save energy and reduce energy consumption. The discrete element method is a numerical approach used to simulate the behavior of granular materials and has been widely applied in the study of mineral processing and crushing processes. This article uses EDEM discrete element software to simulate three different liner structures of ball mills (stepped liner, T-shaped liner, and inclined liner) and analyzes the motion path of grinding balls in the ball mill. At the same time, by evaluating the grinding ball height, power, collision type, collision frequency, and relative velocity of the ball mill, the grinding effect of the three lining plate structures was assessed, and it was found that the stepped lining plate has certain advantages in its grinding effect. The EDEM discrete element simulation is in good agreement with the actual working conditions of the ball mill and has good reference and guidance significance for grinding work.